2022
DOI: 10.32604/cmc.2022.025863
|View full text |Cite
|
Sign up to set email alerts
|

Week Ahead Electricity Power and Price Forecasting Using Improved DenseNet-121 Method

Abstract: In the Smart Grid (SG) residential environment, consumers change their power consumption routine according to the price and incentives announced by the utility, which causes the prices to deviate from the initial pattern. Thereby, electricity demand and price forecasting play a significant role and can help in terms of reliability and sustainability. Due to the massive amount of data, big data analytics for forecasting becomes a hot topic in the SG domain. In this paper, the changing and non-linearity of consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…For the medium-and long-term and short-term prediction methods of electricity price, it is necessary to adopt different prediction models to analyze them, among which the commonly used methods include exponential smoothing method, ARMA model, neural network, etc., and then the relevant structure diagram can be constructed according to the electricity price prediction situation of big data analysis [2][3][4], As shown in Figure Figure 1.…”
Section: Methods Of Electricity Price Risk Prediction Based On Big Da...mentioning
confidence: 99%
“…For the medium-and long-term and short-term prediction methods of electricity price, it is necessary to adopt different prediction models to analyze them, among which the commonly used methods include exponential smoothing method, ARMA model, neural network, etc., and then the relevant structure diagram can be constructed according to the electricity price prediction situation of big data analysis [2][3][4], As shown in Figure Figure 1.…”
Section: Methods Of Electricity Price Risk Prediction Based On Big Da...mentioning
confidence: 99%
“…A large number of studies have shown that the power load has self-similarity and long-term dependence [19,32]. At present, the power load comes from a variety of sources, and is susceptible to external factors such as weather and economy [33,34]. As a result, the increase in non-linearity and instability in power load data makes it challenging to accurately predict power loads [35].…”
Section: Related Workmentioning
confidence: 99%
“…Taheri et al [9] investigated long short-term memory (LSTM) to propose a short, mid, and long-term load forecasting model. Irfan et al [10] developed a DensetNet-121 based week-ahead load forecasting model with a support vector machine (SVM) ensemble to contribute an integration approach for combining multiple networks. Undoubtfully, the above ventures provide a thoughtful insight for electric load forecasting.…”
Section: Introductionmentioning
confidence: 99%